THE INCREASING OPERATIONAL CHARACTERISTICS OF VEHICLE ELEMENTS BY THE USE OF FILLED EPOXY COMPOSITES - Yakushchenko, Serhii; Brailo, Mykola; Zinchenko, Serhii; Sapronova, Anna; Klementiev, Igor (Scientific Journal "Metallurgy", 2023)
The increasing the operational characteristics of vehicle elements by using filled epoxypolyester composite materials was investigated. The composite the ED–20 epoxy diane oligomer (q = 100 wt. %), orthophthalic dicyclopentadiene unsaturated preaccelerated polyester resin ENYDYNE H 68372 TAE – q = 10 wt. % (per 100 weight parts of epoxy resin), polyethylenepolyamine (PEPA) hardener (q = 10 wt. %), Butanox-M50 initiator for polyester resins – (q = 1.5 wt. %) were used to form the polymer matrix. Methylene diphenyl diisocyanate (q = 0.25 wt. %) was used as a modifier. Hexagonal boron nitride (h-NB) – 8-10 μm – (q = 60 wt. %) and mica 20–40 μm (q = 20 wt. %) were used as fillers. A study of tribological properties under conditions of dry friction, lubricating medium was carried out using a friction machine 2070 SMT-1 according to the “disk-pad” scheme in accordance with ASTM G77-17. Test conditions of the developed materials: specific load p = 1 MPa, sliding speed υ = 1,0 m/s, the sliding distance is 10,000 m. The temperature in the contact zone was determined using a chromel-drop thermocouple, the signal from which was recorded by measuring equipment. It has been established that the content of fillers in the epoxypolyester matrix has a positive effect on the tribological properties of the composite. In an experimental study, it was analyzed that the tribological properties of the composite during dry friction in terms of the content of mica and h-BN are improved compared to the epoxy matrix. During the operation of the composite in the conditions of the lubricating medium, the coefficient of friction is – ƒ = 0.05...0.06, the run-in distance – l = 3500...4000 m, the wear rate – Im = 0.27...0.30 mg/km, the contact temperature in the friction area T = 308...310 K. In addition, the friction surface after testing the composite material was studied and the feasibility of using the developed material in the friction nodes of mechanisms that work when lubricated with oil was proved.